APPLICATIONS FOR DETECTING DISEASES IN CHILDREN USING MICROSOFT VISUAL BASIC 6.0 - Rama Dimas Pradhitya (Jurnal Sistem Informasi, 2006)
The growing world of computer technology so that all problems can be solved with a computer, one of which is to create an "Application to Detect Disease in Children", where with this complaint who we can diagnose our children naturally without having to go outside the house to go to the doctor. This application is designed with the view that attention to simplicity in operation.